The representation of unconventional physician in alexander pope’s memories of martinus scriblerus - Ibrahim, Ali; Saeed, Ismael (Humanities Journal of University of Zakho, 2024)
This paper examines Alexander Pope’s Memoirs of The Extraordinary Life, Works, and Discoveries of Martinus Scriblerus (1741) with a central focus on portraying the main character as an unconventional physician. Alexander Pope recognizes the existence of two distinctive consciousness; he aims to awaken society from what is perceived as false consciousness through the main character’s different consciousness. The author presents the main character as an unconventional physician who explores the traces of the imposed social and cultural norms behind the physical and mental illnesses that are inflicted on the population in the fictional society in the story. The physician attempts to cure these diseases by rectifying the impact of societal norms on the individual, considering them the leading causes that hinder an individual’s true authenticity. The article attempts to employ a Marxist criticism approach, specifically relying on the Surplus Value theory, to investigate the source of false consciousness that inflicted the society. Moreover, the theory serves to underscore the economic dimension of false consciousness, emphasizing that the distortion of true identity is not merely a cultural or ideological phenomenon but is deeply intertwined with the economic relations within society. By embracing the dominant values and failing to recognize their role as the primary producers of surplus value that perpetuates a system that inherently disadvantages them, Pope aims to awaken the population. The article concludes that the main character, advocating for individual liberation from false consciousness, supports the idea that two distinctive types of consciousness exist. Also, it concludes that the main character, as a holder of class consciousness, emerges as a symbolic dissenter and, through his treatments, rejects the dominant culture, perceiving it to be the reason that hinders the individual’s self-realization and authenticity. Also, it concludes that the main character is involved in a conflict with the broader society, leading him to be isolated and feel a lack of belonging due to his different consciousness.